FACTORS RELATED TO DIET COMPLIANCE IN ELDERLY PARENTS WITH TYPE 2 DIABETES MELLITUS IN THE WORK AREA OF MOJOLANGU COMMUNITY HEALTH CENTER - Citra, Fiona; Subekti, Imam; Dyah C, Maria; Marsaid, Marsaid (Indonesian Journal of Applied Health, 2025)
Introduction: The increasing incidence of type 2 diabetes mellitus can be caused by various factors, namely gender, education, knowledge, and family support. The aim of the study was to determine the factors associated with dietary compliance in the elderly with type 2 diabetes mellitus at the Mojolangu Health Center. Method: This research is a type of quantitative research using a cross sectional design. The sampling technique used was a purposive sampling technique with a total sampling of 40 respondents. The independent variable factors related to dietary adherence are gender, education, knowledge, and family support and the dependent variable is DM dietary adherence. Results: The results showed that 32 respondents (80%) adhered to the DM diet and 8 respondents (20%) did not comply. From the results of the chi-square correlation test, it was found that the p value was 0.237 > 0.05 indicating that there was no relationship between gender and diet adherence to type 2 DM. The results of the Spearman rho test showed that there was a relationship between education (p value = 0.047, r = -0.316), knowledge (p value = 0.003, r = 0.454), and family support (p value = 0.003, r = 0.445) with dietary compliance with type 2 DM. Conclusion: Factors associated with dietary compliance in the elderly with type 2 diabetes mellitus are education, knowledge, and family support. Suggestion: It is hoped that the Mojolangu Health Center can improve health services for the community, such as providing education about adherence to the DM diet through electronic media, such as showing interesting educational videos when control patients are in the poly.